The enhancement of explosive power contributes to the development of anaerobic capacity: A comparison of autoregulatory progressive resistance exercise and velocity-based resistance training - Huang, Z.; Chen, J.; Chen, L.; Zhang, M.; Zhang, W.; Sun, J.; Li, D. (Journal of Exercise Science & Fitness, 2024)
Background/Objectives Due to the character of the taekwondo, the adenosine triphosphate-phosphocreatine system provides the energy for each kick, the glycolytic system supports the repeated execution of kicks, and the aerobic system promotes recovery between these movements and the bout. Therefore, taekwondo athletes require high explosive power and anaerobic capacity in order to carry out sustained and powerful attacks. So, the purpose of this study is to compare the effects of APRE and VBRT on lower-limb explosive power and anaerobic capacity in college taekwondo players.